Triheptanoin: long-term effects in the very long-chain acyl-CoA dehydrogenase-deficient mouse - Sara Tucci; Ulrich Floegel; Frauke Beermann; Sidney Behringer; Ute Spiekerkoetter (Journal of Lipid Research, 2017)
A rather new approach in the treatment of long-chain fatty acid oxidation disorders is represented by triheptanoin, a triglyceride with three medium-odd-chain heptanoic acids (C7), due to its anaplerotic potential. We here investigate the effects of a 1-year triheptanoin-based diet on the clinical phenotype of very long-chain-acyl-CoA-dehydrogenase-deficient (VLCAD−/−) mice. The cardiac function was assessed in VLCAD−/− mice by in vivo MRI. Metabolic adaptations were identified by the expression of genes regulating energy metabolism and anaplerotic processes using real-time PCR, and the results were correlated with the measurement of the glycolytic enzymes pyruvate dehydrogenase and pyruvate kinase. Finally, the intrahepatic lipid accumulation and oxidative stress in response to the long-term triheptanoin diet were assessed. Triheptanoin was not able to prevent the development of systolic dysfunction in VLCAD−/− mice despite an upregulation of cardiac glucose oxidation. Strikingly, the anaplerotic effects of triheptanoin were restricted to the liver. Despite this, the hepatic lipic content was increased upon triheptanoin supplementation. Our data demonstrate that the concept of anaplerosis does not apply to all tissues equally.